2011
DOI: 10.30970/sbi.0502.155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide donor on viability of human leukemic cells upon arginine deprivation

Abstract: Some types of tumor cells are unable to synthesize arginine from its precursors. They exhibit growth inhibition and decreased viability in vitro and in vivo under enzymatic arginine deprivation. However, prolonged arginine starvation in human may cause vasoconstriction and thrombosis due to the deficit of arginine derivative, nitric oxide (NO), as vasodilator and disaggregant. This problem can be overcome via supplementation with exogenous NO-donors in vivo, which, in turn, may produce either, pro-apoptotic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…However, why exogenous NO is more cytotoxic for non-proliferating arginine-deprived than for proliferating in the CM cancer cells remains to be elucidated. It is necessary to stress that similar effect was observed in our previous study on Jurkat cells incubated in defined arginine-free medium [5].…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…However, why exogenous NO is more cytotoxic for non-proliferating arginine-deprived than for proliferating in the CM cancer cells remains to be elucidated. It is necessary to stress that similar effect was observed in our previous study on Jurkat cells incubated in defined arginine-free medium [5].…”
Section: Resultsmentioning
confidence: 55%
“…In our previous study we found that SNP, a NO donor, does not counteract apoptotic cell death and, in fact, increases cytotoxic effect of arginine deprivation for Jurkat leukemic cells in defined arginine-free medium [5]. We also demonstrated that rhARG treatment alone is relatively harmless for normal PBL [4].…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…With this respect, we recently observed that deficit of arginine specifically destabilizes actine cytoskeleton in glioma cells and decreases their motility and clonogenic potential (Pavlyk et al, ). It was also found that supplementation of exogenous nitric oxide donor, as a potential attenuating therapeutic compound, does not rescue tumor cells from the effects of arginine deprivation stress (Chen et al, ). Very recent reports also point at a possible ASS role as tumor suppressor (Huang et al, ; Allen et al, ), opening yet new possibilities and stimulating the development of arginine deprivation as an efficient anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%